2020
DOI: 10.1101/2020.12.02.20234989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying US Counties with High Cumulative COVID-19 Burden and Their Characteristics

Abstract: Identifying areas with high COVID-19 burden and their characteristics can help improve vaccine distribution and uptake, reduce burdens on health care systems, and allow for better allocation of public health intervention resources. Synthesizing data from various government and nonprofit institutions of 3,142 United States (US) counties as of 12/21/2020, we studied county-level characteristics that are associated with cumulative case and death rates using regression analyses. Our results showed counties that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
4
1
Order By: Relevance
“…Although six other studies [42][43][44][45][46][47] found a relationship between measures of structural racism and racial disparities in COVID-19 mortality at the county level, this paper documents such a relationship at the state level. This finding is important because it is at the state level that most power resides to enact or refine laws related to public health and safety that could directly impact these observed disparities [48].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Although six other studies [42][43][44][45][46][47] found a relationship between measures of structural racism and racial disparities in COVID-19 mortality at the county level, this paper documents such a relationship at the state level. This finding is important because it is at the state level that most power resides to enact or refine laws related to public health and safety that could directly impact these observed disparities [48].…”
Section: Discussioncontrasting
confidence: 55%
“…With national age-adjusted death rates revealing an even more profound racial disparity in COVID-19 mortality, it is even more crucial to determine the reasons for these disparities. Although many papers have suggested that structural racism is a critical factor in explaining racial disparities in COVID-19 mortality, we are aware of only six that have demonstrated this relationship empirically by explicitly measuring structural racism [42][43][44][45][46][47]. Tan et al [42] examined the relationship between four measures of structural racism (residential segregation and differences in incarceration rates, economic status, and employment status) and county-level COVID-19 death rates, finding that the degree of residential segregation was significantly related to higher overall death rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, it also has disproportionately affected minority and underserved populations, where COVID-19 infection and fatality rates are significantly higher among African American and Hispanic populations [1][2][3]. Previous studies have shown various social determinants of health (SDOH) that may explain the disparity in COVID-19 incidence and mortality in ethnic and racial minorities [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The geographical scale of the US county often lacks granularity to reveal the local spatial pattern and detect local hot spots (ie, areas with excessive infection rates). Moreover, the high variability of SDOH within a county population was not able to accurately examine the impact of SDOH on COVID-19 disparities in populations [5]. Studies that investigate the SDOH and COVID-19 incidence and mortality at a geographical scale smaller than the US county are limited [7,8].…”
Section: Introductionmentioning
confidence: 99%